PEMBELAJARAN FISIKA DENGAN COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENGOPTIMALKAN AKTIVITAS DAN KEMAMPUAN KOGNITIF SISWA KELAS X-6 SMA MTA SURAKARTA - Musthofa, Khoirul; Sar, Sarwanto; Fitriana, Dyah (Jurnal Pendidikan Fisika, 2013)
The purpose of the application cooperative learningâs model is increasing learning activity and physics cognitive skill of class X-6 of SMA MTA SURAKARTAâs students 2011/2012 through the application of cooperative learning type jigsawâs model in the process of learning physics. The research used Classroom Action Research (CAR) method. Each cycle in CAR is started with plan, then continued with implementation, observation and reflection. The subjects of the research are 32 students of class X-6 of SMA MTA SURAKARTA 2011/ 2012. The data are collected through observation using the students learning activity observation sheet and documentation research from the result of students cognitive test, then it is analyzed ina descriptive qualitative manner. From the result of the research, it can be conclude that the implementation of Cooperative Learning Type Jigsawâs model can increase the learning activity and cognitive skill of the students of class X-6 of SMA MTA SURAKARTA 2011/ 2012Â  in the process of learning physics. By emphasizing the treatment to the chance giving to the students to deliver their idea or opinion in the group discussion inside and outside the class, especially in the dormitory, and active in seeking and utilizing a variety of learning resources, so it can be seen that instudentâs learning activitiesof learning processÂ  in the initial condition is always increase in the first and second cycle. By limiting score of 60, the percentage of completeness on the initial conditionsof student learning activity by 12.5%, then in the first cycle become 50% and in the second cycle increase up to 84.375%. Similarly, the aspects of studentâs cognitive abilities are always increase. By emphasizing on the actionin the form of mentoring and group discussion learning both inside and outside the classroom, especially in the dormitory, Alpha and optimizing the use of learning resources, especially books and the internet, so it can be seen that there is an increase in students cognitive abilities with the passing grade of 70. In the initial condition the percentage of the completeness of students test result by 18,75 %, then increase in the first cycle by 25%, and increase again by 72% in the second cycle. Â  Keyword: cooperative learning, Jigsaw, learning activity, cognitive ability.